Analisis Pengaruh Beban Berlebih terhadap Sisa Umur Perkerasan Lentur pada Jalan Kawasan Industri Driyorejo dengan Metode MDPJ 2017 - Misela, Adinda; Sholichin, Ibnu; Estikhamah, Fithri (Universitas Batanghari Jambi, 2024)
Flexible pavement is designed with regard to the load that will be received in order to achieve optimal performance throughout its service life. However, conditions in the road reveal indications of overloading by each category of vehicles, especially overload vehicles. Driyorejo industrial area road is a provincial road that connects the main industrial areas in Gresik Regency. With traffic dominated by overload vehicles, especially large trucks carrying a lot of goods, indications of damage to the pavement are becoming increasingly clear and obvious. This research aims to assess the impact of traffic load on the remaining life expectancy of flexible pavement, focusing on the load of vehicles crossing the road in the Driyorejo industrial area as the study variable. The calculation method used is the Bina Marga 2017 Method. The data used are Average Daily Traffic (LHR) data and vehicle load data. From the calculation results, the actual traffic growth (i) value is 32.7%. Vehicle overloading causes a decrease in the planned life of the road as indicated by the truck factor value of 1.06. The Remaining Life (RL) calculation represents a 14% decrease from the standard RL value of 69.3% to 55.3% under overload conditions, so it can be concluded that the overload significantly reduces the life of the road which was originally designed for 10 years to only 7 years.